Long term outcomes of daily oral vs. pulsed intravenous cyclophosphamide in a non-trial setting in ANCA associated vasculitis - La-Crette, Jonathan; Royle, Jeremy; Lanyon, Peter C.; Ferraro, Alastair; Butler, Amanda; Pearce, Fiona A. (Springer, 2017)
Objectives We aimed to compare risk of death, relapse, neutropenia and infection requiring hospital admission between unselected ANCA-associated vasculitis (AAV) patients according to whether cyclophosphamide induction was by daily oral (PO) or pulse intravenous (IV) route. Method We identified all newly-diagnosed AAV patients treated with PO or IV cyclophosphamide between March 2007 and June 2013. We used Cox and logistic regression models to compare mortality, relapse and adverse events, and adjusted these for age, renal function and other significant confounders. Results 57 patients received PO and 57 received IV cyclophosphamide. One year survival was 86.0% in PO and 98.2% in IV patients; all-time adjusted hazard ratio (HR) for PO compared to IV cyclophosphamide was 1.8 (95% CI 0.3-10.6, P=0.54). One-year relapse-free survival was 80.7% in PO compared to 87.3% in IV patients, all-time adjusted HR 3.8 (0.2-846, P=0.37). During the first 12 months neutropenia of ≤0.5x10⁹/L occurred in 9 (16%) PO and 0 (0%) IV cyclophosphamide patients (p=0.003). The number of patients admitted with one or more infections was 16 (28%) in the PO group and 9 (16%) in the IV group, adjusted OR 2.2 (0.6-8.6, p=0.23). Conclusions. We observed an increased risk of neutropenia, and a trend towards increased risk of death, and admission with infection with PO cyclophosphamide. This adds certainty to previous studies, indicating that PO administration induces greater marrow toxicity. Infection-related admissions within 12 months of starting cyclophosphamide were higher than in clinical trials, possibly reflecting the unselected nature of this cohort.